POLITICAL AND LEGAL ASPECTS OF GENDER POLICY IN THE MODERN WORLD - Andirzhanova Gulnar; Tleuzhanova Aiymgul; Li Elizaveta; Dulatov Gabit (European Scientific Journal, ESJ, 2014)
The rights of women and development of the person are among the most important social problems of the new millennium. Everyday life of women has huge impact on all society, their situation is a sensitive indicator of development of humanity as a whole. They began to play a crucial role in ensuring wellbeing of children and the main role in providing a survival of a family, the female consciousness grew, social movements began to be formed. At present the governments of a number of the countries of the world seriously perceive all recommendations of the international community and try by means of special acts and practical measures to establish balance in social positions of men and women in the countries. In this article analyzed problems of political legal support and protection of the rights of women in the modern interstate cooperation, actual theoretical and practical problems of gender equality in the conditions of globalization.